2007
DOI: 10.1093/aje/kwk119
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Validity of the Shanghai Men's Health Study Physical Activity Questionnaire

Abstract: Reproducibility and validity of the physical activity questionnaire (PAQ) used in the Shanghai Men's Health Study (2003-2006, People's Republic of China) was evaluated in a random sample of 196 participants aged 40-74 years. Participants completed a PAQ at baseline and again 1 year later, 12 monthly 7-day physical activity recalls, and four quarterly 1-week physical activity logs. Reproducibility was evaluated by using the two PAQs and validity by comparing the PAQs with 1-year averages of the two criterion me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 38 publications
4
47
1
Order By: Relevance
“…However, previous validation studies have been shown that the SWHS and SMHS physical activity questionnaires can capture the exercise information accurately and reliably. 8,9 Since this study was conducted in a single metropolitan area, Shanghai, the results may not be generalizable to other cities, particularly rural areas or regions of China, because the t'ai chi practice may vary. Also, generalizing results globally is difficult due to potential variations in how t'ai chi is practiced, perceived, or learned indigenously in China as compared to other countries.…”
Section: T'ai Chi For Middle-aged and Elderly In Urban Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous validation studies have been shown that the SWHS and SMHS physical activity questionnaires can capture the exercise information accurately and reliably. 8,9 Since this study was conducted in a single metropolitan area, Shanghai, the results may not be generalizable to other cities, particularly rural areas or regions of China, because the t'ai chi practice may vary. Also, generalizing results globally is difficult due to potential variations in how t'ai chi is practiced, perceived, or learned indigenously in China as compared to other countries.…”
Section: T'ai Chi For Middle-aged and Elderly In Urban Chinamentioning
confidence: 99%
“…The instrument used to assess physical activity has been validated for both women and men. 8,9 Initially, subjects were asked if they had participated in regular exercise, defined as at least once a week for at least 3 consecutive months, during the past 5 years (yes, no) prior to the survey. Subjects who reported regular exercise were then asked details regarding up to three exercises/sports, including type of exercise/sports, frequency (hours per week), and duration (years of practice) in the past 5 years.…”
Section: Data Sourcementioning
confidence: 99%
“…Detailed assessment of physical activity was collected by using validated questionnaires (21,22). The questionnaires evaluated regular exercise and participation in sports during the 5 y preceding the interview, daily activity, and the daily commute to and from work.…”
Section: Other Factors As Potential Confoundersmentioning
confidence: 99%
“…25 The questionnaire evaluated physical activity during the 5 years preceding the interview, (yes/no), hypertension (blood pressure ≥85/130 mmHg and/or taking hypertension medication), and cardiovascular disease (CVD) at baseline (yes/no).…”
Section: Physical Activitymentioning
confidence: 99%